Hubungan antara status tumor budding dengan berbagai parameter klinikopatologi pada adenokarsinoma kolorektal di RSUP Sanglah, Bali, Indonesia - Luh Putu Iin Indrayani Maker; Ni Putu Sriwidyani (Intisari Sains Medis, 2021)
Background: Colorectal malignancies are common, with adenocarcinoma as the most prevalent type. Recently, studies of specific morphology like tumor budding have already started and related with tumor’s aggressivity as well as several parameters. This study aims to evaluate the association between tumor budding grade with patient age, sex, tumor location, histological grade, depth of invasion, and nodal status in colorectal adenocarcinoma at Sanglah General Hospital.Methods: This cross-sectional descriptive study used samples of intestinal resection specimens accompanied by Regional Lymph Node (RLN) removal of colorectal adenocarcinoma patients at Sanglah Hospital in 2018-2020. The sampling technique was carried out consecutively, which met the inclusion and exclusion criteria. Data on age, sex, tumor location, histologic grade, depth of invasion, and nodal status were obtained from the archives of examination results. At the same time, tumor budding data were obtained from observations of histopathological preparations with Hematoxylin-Eosin (H&E) staining. The results of the observations were tested statistically and presented descriptively. Data were analyzed with Chi-Square using SPSS version 22 for Windows.Results: Most of the study samples were 50 years old (84.0%), followed by male gender (62.0%), tumor location in the left colon (67.0%), low-grade (90.0%), T3-T4 invasion depth (77.0%), negative nodal status (60.0%), and high-tumor budding grade (51.0%). The Chi-Square test showed a significant relationship between the depth of invasion (p=0.001) and nodal status (p=0.009) variables on tumor budding grade.Conclusion: There were significant correlations between tumor budding grade and depth on invasion and nodal status. Latar Belakang: Kanker kolorektal merupakan keganasan yang sering ditemukan dengan adenokarsinoma merupakan tipe histopatologi terbanyak. Dewasa ini telah mulai diteliti morfologi spesifik yaitu tumor budding yang dikaitkan dengan agresivitas tumor maupun parameter lainnya. Penelitian ini bertujuan untuk mengetahui hubungan antara tumor budding grade dengan umur pasien, jenis kelamin, lokasi tumor, grade histopatologi, kedalaman invasi, dan status nodal pada adenokarsinoma kolorektal di RSUP Sanglah Denpasar.Metode: Penelitian deskriptif potong lintang ini menggunakan sampel spesimen reseksi usus disertai pengangkatan Kelenjar Getah Bening (KGB) regional pasien adenokarsinoma kolorektal di RSUP Sanglah tahun 2018-2020. Teknik pengambilan sampel dilakukan secara konsekutif, yang memenuhi kriteria inklusi dan eksklusi. Data umur, jenis kelamin, lokasi tumor, grade histopatologi, kedalaman invasi dan status nodal diperoleh dari arsip hasil pemeriksaan. Sedangkan data tumor budding diperoleh dari pengamatan sediaan histopatologi pewarnaan Hematoksilin-Eosin (H&E). Hasil pengamatan diuji secara statistik dan ditampilkan secara deskriptif. Data dianalisis dengan Chi-Square menggunakan SPSS versi 22 untuk Windows.Hasil: Sebagian besar sampel penelitian berusia ? 50 tahun (84,0%), diikuti dengan jenis kelamin laki-laki (62,0%), lokasi tumor pada kolon kiri (67,0%), low-grade (90,0%), kedalaman invasi T3-T4 (77,0%), status nodal negatif (60,0%), dan high-tumor budding grade (51,0%). Uji Chi-Square menunjukkan bahwa terdapat hubungan yang bermakna antara variabel kedalaman invasi (p=0,001) dan status nodal (p=0,009) terhadap tumor budding grade.Kesimpulan: Terdapat hubungan yang bermakna antara tumor budding grade dengan kedalaman invasi dan status nodal adenokarsinoma kolorektal.